The Relationship between Knowledge and Self-Medication Practices for Dysmenorrhea among Female Students of SMK Negeri 2 Palembang - Kamalia Layal; Syarinta Adenina; Septi Purnamasari; Ayeshah Augusta Rosdah; Msy Rulan Adnindya (Sriwijaya Journal of Medicine, 2024)
Dysmenorrhea is a common occurrence in most women. The pain arising from dysmenorrhea ranges from mild to moderate and can disrupt daily activities and performance. Many women practice self-medication to alleviate this pain. This self-medication practice is influenced by several factors, one of which is the level of knowledge. This study aims to explore the relationship between the level of knowledge among female students and self-medication behavior in dysmenorrhea. This study used a cross-sectional design with a random sampling of female students from SMK Negeri 2 Palembang. The total sample involved 41 students. Data were collected and analyzed using chi-square and Mann-Whitney U tests. The majority of students experienced dysmenorrhea (87.8%) with an average Visual Analog Scale (VAS) score of 4.6. The duration of pain varied, with most experiencing pain for 2-3 days after menstruation. Almost all students (97.6%) had good or sufficient knowledge about dysmenorrhea. However, only a few students practiced self-medication (11.1%), with paracetamol being the most commonly used medication. The analysis showed a significant relationship between knowledge level and self-medication behavior (p=0.002, OR: 12.681). The level of knowledge among female students is significantly associated with self-medication behavior in dysmenorrhea. Better health education on dysmenorrhea management and the use of safe medication needs to be strengthened to reduce the risk of side effects and improve the well-being of students.